The hypocrisy: it’s reasons and the ways to prevent it in the intent of the noble Qur’an. - Ammar Latif Majid - Makarem Tarjoman ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The subject of the study is the hypocrisy and its reasons and the ways to prohibit it. The author aims in this study to verify the definition of hypocrisy and the linguistic derivation of the hypocrisy Word also verify the idiomatic meaning of it. In this paper, the concept of hypocrisy has been searched and its prosperities which mentioned by Qur’an and its reasons and the ways to prevent it. The author confirm that the new material in this study was the verification of the reasons which lead to the hypocrisy and explaining the methods that can prevent the hypocrisy. also the way of dealing with the hypocrisy according the Qur’an’s concept. As a result, the author shows that there is a misdemeanant reasons and actional reasons.